USE OF THE QUR’AN VERSES BEHIND ONTOKUSUMO’S VEST: A LIVING QUR’AN OF THE LOCAL WISDOM OF THE JAVANESE COMMUNITY - Akbar, Muhammad Syahrul (Universitas Nurul Jadid, 2022)
A talisman is anything that is believed to have power and is also believed to be an heirloom with magical powers that can help solve various life problems. In its classification, amulets are divided into syar’i and non-syar’i amulets. Syar’i amulets use the verses of the Qur’an and Allah’s names in the manufacture and arrangement as well as clear meaning when written or read, one of which is an heirloom in the form of an Ontokusumo Vest, which is one of the relics of Sunan Kalijaga which is trusted by the community as amulets that aim to protect themselves. In Probolinggo, community leaders are still preserving the Doubling of the Ontokusumo Vest. In the study of the living Qur’an, how does it relate to the text of the holy book? This research was written to explain and analyze the mysteries of these objects related to the verses of the Qur’an. Through the living Qur’an method, this research seeks to explain how the verses of the Qur’an relate to the mystery of Ontokusumo vest, which is widespread in the archipelago, including in Probolinggo. With this research, it is known that the ones that have a significant influence on the mystery of the Ontokusumo Vest are selected verses of the Qur’an; Basmalah, Ayat Kursi, and Al-Falaq.